1990
DOI: 10.1093/jnci/82.15.1272
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Mendelian Inheritance in the Pathogenesis of Lung Cancer

Abstract: Segregation analyses that allowed for variable age of onset of lung cancer and smoking history were performed on 337 families, each ascertained through a lung cancer proband. Results indicated compatibility of the data with mendelian codominant inheritance of a rare major autosomal gene that produces earlier age of onset of the cancer. Segregation at this putative locus could account for 69% and 47% of the cumulative incidence of lung cancer in individuals up to ages 50 and 60, respectively. The gene was invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
98
0
6

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(113 citation statements)
references
References 0 publications
9
98
0
6
Order By: Relevance
“…The existence of genetic susceptibility to lung cancer is suggested in a number of familial aggregation studies [4][5][6]8,[15][16][17][18][19] as well as in segregation analyses [20][21][22][23][24] and in a linkage study 25 Familial risks may reflect not only genetic predisposition, but also shared exposures, such as smoking habits, [27][28][29] or exposure to cooking fumes. 7,30 To address this issue, we (i) included only relatives of never-smoking probands; (ii) took into account smoking habits of the relatives, both by controlling for smoking status and by conducting analyses stratified by smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of genetic susceptibility to lung cancer is suggested in a number of familial aggregation studies [4][5][6]8,[15][16][17][18][19] as well as in segregation analyses [20][21][22][23][24] and in a linkage study 25 Familial risks may reflect not only genetic predisposition, but also shared exposures, such as smoking habits, [27][28][29] or exposure to cooking fumes. 7,30 To address this issue, we (i) included only relatives of never-smoking probands; (ii) took into account smoking habits of the relatives, both by controlling for smoking status and by conducting analyses stratified by smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…Existem evidências de que a hereditariedade tenha um peso nesse processo. Não há conhecimento preciso sobre marcadores genéticos envolvidos com o câncer do pulmão, mas estudos recentes o têm relacionado a uma alteração do citocromo 450 e do cromossomo 22 (54) .…”
Section: Ix) Fatores Genéticosunclassified
“…Furthermore, Tokuhata and Lilienfeld ( 19) reported that lung cancer among relatives of patients with lung cancer are 2.7 times greater than that amongrelatives of controls. Segregation analysis further suggests that Mendelian inheritance of a rare major autosomal gene mayproduce lung cancer at an earlier age of onset (20 mainly participated in familial occurrence of lung cancer, since i) smoking indexes were not very high in these patients, ii) ovarian cancer was present in one patient, and iii) the onset of lung cancer wasobserved in relatively younger ages. The coexistence of idiopathic pulmonary fibrosis (IPF) and carcinoma of the lung, especially BAC, is well known (9).…”
Section: Discussionmentioning
confidence: 97%